2020
DOI: 10.3390/v12070761
|View full text |Cite
|
Sign up to set email alerts
|

Low Host Abundance and High Temperature Determine Switching from Lytic to Lysogenic Cycles in Planktonic Microbial Communities in a Tropical Sea (Red Sea)

Abstract: The lytic and lysogenic life cycles of marine phages are influenced by environmental conditions such as solar radiation, temperature, and host abundance. Temperature can regulate phage infection, but its role is difficult to discern in oligotrophic waters where there is typically low host abundance and high temperatures. Here, we study the temporal variability of viral dynamics and the occurrence of lysogeny using mitomycin C in a eutrophic coastal lagoon in the oligotrophic Red Sea, which showed strong season… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
14
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 79 publications
(147 reference statements)
7
14
3
Order By: Relevance
“…The BS was assessed from viruses produced during five of the incubations. BS was then calculated by subtracting the produced virus (VPc) in the untreated control samples from the number of produced virus in the virusreduced samples (VPr), which demonstrates the net increase in the number of phages that were released from infected bacteria, and then dividing by the number of bacteria killed (Bdead) during the incubations by infection [26], as follows:…”
Section: Burst Size and The Percentage Of Lysogenic Heterotrophic Bacteriamentioning
confidence: 99%
See 2 more Smart Citations
“…The BS was assessed from viruses produced during five of the incubations. BS was then calculated by subtracting the produced virus (VPc) in the untreated control samples from the number of produced virus in the virusreduced samples (VPr), which demonstrates the net increase in the number of phages that were released from infected bacteria, and then dividing by the number of bacteria killed (Bdead) during the incubations by infection [26], as follows:…”
Section: Burst Size and The Percentage Of Lysogenic Heterotrophic Bacteriamentioning
confidence: 99%
“…Reference [25] reported that the high temperature between 31 and 34 • C of the Red Sea was responsible for raising the rates of zooplankton mortality. We tested recently the role of water temperature on viral dynamics and the shift from lysogeny to lytic replication cycles in the Red Sea in a mesotrophic coastal lagoon in the Red Se [26]. The coastal lagoon is a shallow environment separated from the open waters by the reef system, where seawater temperature reached high values (≥33.3 • C) and where we observed that lysogeny occurred in a small percentage at the end of the summer when the temperature was highest and host was low [26].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The impact of temperature, and understanding whether host maximum growth rate potential affects viral replication, also remain important unknowns; do slow-growing hosts have longer latent periods, or do viruses push the host physiology into overdrive, such that LP is never very long? Winter et al (2012) attempted to use an artificial neural network approach to link intrinsic and extrinsic factors to virus growth dynamics, to rather mixed effect; it did identify the importance of temperature changes, likely linking virus-host dynamics to upshocks in host physiology with temperature increases (Demory et al, 2017;Maat et al, 2017;Ashy and Agusti, 2020;Frenken et al, 2020). Additionally, Mojica and Brussaard (2014, their Table 1) document some temperature interactions with virushost dynamics, but temperature and climate change in general will also affect the type of hosts that dominate both directly and indirectly via impacts on their grazers and nutrient regenerators (Frenken et al, 2020).…”
Section: Models and Datamentioning
confidence: 99%
“…Therefore, the Red Sea offers the opportunity to investigate potential acclimatization and realized adaptation to ocean warming, with a large number of studies addressing its coral reef habitats (Sawall and Al-Sofyani, 2015;Ziegler et al, 2019) and symbionts responses (Hume et al, 2016). It also constitutes a unique opportunity to identify adaptation mechanisms, and physiological and molecular responses to warming (Hume et al, 2016;Giomi et al, 2019;Anton et al, 2020a) including how the elevated temperature may affect biological processes and the interactions between organisms (Hume et al, 2016;Silva et al, 2018;Abdulrahman Ashy and Agustí, 2020;Anton et al, 2020b).…”
Section: Introductionmentioning
confidence: 99%